A preliminary study on the human body aura for smoker and non smoker using resonant field imaging (RFI) / Haslina Hashim - Hashim, Haslina (2011)
This paper present a preliminary study on the human body aura condition for smoker and non smoker using Resonant Field Imaging (RFI) system. This research involves 30 samples which 15 samples are smoker and the rest are non smoker. During this research, six point of the human body's frequency mainly focus on chakra area was recorded using RFI. The data was analyzed using aura interpretation for Human Body software by converting the frequency into color, Energy field Score and categorized the frequency. The results demonstrate that 33% of non smoker are in excellent group whereby none of smoker falls into this group. This finding indicate that non smoker have higher energy field score as compared to smoker. Consequently, non smoker in particular are generally healthier than smoker.